Change Management in Health Care. Issue 2 (April 2020) - Campbell, Robert James
Abstract : This article introduces health care managers to the theories and philosophies of John Kotter and William Bridges, 2 leaders in the evolving field of change management. For Kotter, change has both an emotional and situational component, and methods for managing each are expressed in his 8-step model (developing urgency, building a guiding team, creating a vision, communicating for buy-in, enabling action, creating short-term wins, don't let up, and making it stick). Bridges deals with change at a more granular, individual level, suggesting that change within a health care organization means that individuals must transition from one identity to a new identity when they are involved in a process of change. According to Bridges, transitions occur in 3 steps: endings, the neutral zone, and beginnings. The major steps and important concepts within the models of each are addressed, and examples are provided to demonstrate how health care managers can actualize the models within their health care organizations.